Unveiling the Nexus: Elevating marketing strategies for enhancing satisfaction and loyalty in elderly health care services - Bishal Bhuyan (ACHSM, 2024)
The study aimed to examine whether there is an association of marketing mix, and perception with customer's satisfaction, and loyalty among elderly people. A total of 400 participants were included in the study. The study population comprised individuals aged 65 years and above from Assam, India including both males and females. Participants were primarily selected from residential homes, old age homes, and various common gathering places such as parks, shops, Namghar (a holy place), and community halls. The study indicated a significant correlation between the dimensions of the marketing mix, perception, satisfaction, and loyalty. Moreover, the findings from the linear regression analysis, revealed customer satisfaction towards the marketing of healthcare services can be attributed to product, price, place, process, and physical evidence (7 P's) and customer perception (R2=.54; .53 respectively). Additionally, customer loyalty towards the marketing of healthcare services is influenced by product and price (7P's), and customer perception (R2=.54; .2 respectively). This study contributes to understanding the overlooked aspect of marketing to the elderly population, providing valuable insights for healthcare companies to develop improved marketing strategies. Hence, irrespective of the organization's size, type, or location, whether it's a startup or an established entity, privately owned or government-operated, local or global, the role of business managers is vital in making informed decisions and establishing strategic priorities to allocate resources efficiently in order to meet evolving customer demands and achieve business success. As a result, commercial enterprises need to develop tools, concepts, and strategies to effectively navigate the dynamic and unpredictable marketing landscape.